LEFT VENTRICULAR ANEURYSM - Mufti, Waqar A. (Journal of Ayub Medical College Abbottabad, 1995)
Post infarction true ventricular aneurysm may be defined as a localized area of dyskinesia with regional systolic expansion. The definition from surgical observation leads to the following criteria: the presence of a scar like deformity of the ventricular wall, the presence of akinesia or dyskinesia, myocardial thinning or scar formation and the loss of trabecular pattern of the endocardium. It has become common clinical practice to classify ventricular aneurysms with an external bulge as true or false. The wall of the true aneurysm is derived from the myocardium itself whereas the wall of the false aneurysm (pseudoaneurysm) is derived from the pericardium 2. The reported incidence of left ventricular aneurysm (LVA) ranges from 35% to 40%. This wide range is partly a reflection of a lack of generally applied definitions 2'3. Aneurysm formation probably occurs within 3 months after the acute myocardial infarction (AMI) but has been reported to be two weeks to two years after AMI3. Factors such as a large transmural AMI and first AMI have been associated with LVA 4. The greatest risk of aneurysm follows infarction in the area supplied by the left anterior descending artery